2015
DOI: 10.1186/s13019-015-0236-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function before and after the Nuss procedure in adolescents with pectus excavatum: correlation with morphological subtypes

Abstract: BackgroundDifferences in post-Nuss procedure pulmonary function based on the pectus excavatum subtype have not been investigated in adolescents. We evaluated differences in pulmonary function before and after the Nuss procedure according to preoperative morphology.MethodsWe performed a retrospective review of eighteen male patients who had undergone the Nuss procedures. There were nine patients each with symmetric and asymmetric morphology. Patients were younger than 18 years and had no history of respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Further studies focusing on the physical condition of patients in the longterm follow-up are needed. It is not entirely clear whether the improvement in exercise tolerance in the postoperative course, which is often described by the patients and which has also been documented by other authors, is due to a real improvement in cardiopulmonary function or merely to the fact that patients with a corrected deformity are more readily willing to participate in sports [14,15]. In the present study's preoperative cardiopulmonary work-up, no significant respiratory problems were identified that were directly associated with the chest wall deformity or could explain the symptoms the patients reported in preoperative interviews.…”
Section: Discussionmentioning
confidence: 82%
“…Further studies focusing on the physical condition of patients in the longterm follow-up are needed. It is not entirely clear whether the improvement in exercise tolerance in the postoperative course, which is often described by the patients and which has also been documented by other authors, is due to a real improvement in cardiopulmonary function or merely to the fact that patients with a corrected deformity are more readily willing to participate in sports [14,15]. In the present study's preoperative cardiopulmonary work-up, no significant respiratory problems were identified that were directly associated with the chest wall deformity or could explain the symptoms the patients reported in preoperative interviews.…”
Section: Discussionmentioning
confidence: 82%
“…Sigalet et al (5) measured reduced dynamic pulmonary function, forced vital capacity (FVC), forced expiratory volume in 1 second (FEV 1 ), and vital capacity (VC) following Nuss repairs of PE. Jeong et al (19) also reported significantly decreased FVC, FEV 1 , and VC values after the Nuss procedure in adolescents with PE. These authors thought that this reduced pulmonary function was due to short period for steel strut reshaping of the chest wall (5,20).…”
Section: Discussionmentioning
confidence: 90%
“…These results may be related to the morphological asymmetry of the thoracic cavity. Jeong et al ’s study with adolescents treated with the Nuss procedure reported that the reduction of peak expiratory flow and inspiratory cavity was more prominent in patients with the asymmetric type ( 18 ). According to the Blickman et al ’s study, addressing asymmetry in patients with pectus excavatum can improve the pulmonary ventilation-perfusion ratio ( 19 ).…”
Section: Discussionmentioning
confidence: 99%